Sosyal Pazarlama Çerçevesinde Türkiye'deki AIDS'le Mücadele Konulu Reklamların İçerik Analizi - (:unkn) unknown (My University, 2002)
0

AIDS is a serious disease which causes increasing amount of victims day by day. Firms realising this fact, are implementing social campaigns to make people more conscious against this fatal disease. But such campaigns are too sensitive in terms of the correct selection of target market and whether appling emotional or imformational content, etc.